From Tauhid to Social Responsibility: An Integrative Framework of Character Formation in Islamic Religious Education - Uswatun Suciati; Rifqi Khairul Anam (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Character education has become a major concern in contemporary education due to increasing challenges related to moral degradation, social intolerance, and the weakening of ethical responsibility among young people. Although numerous studies have examined the role of Islamic Religious Education (PAI) in character development, existing discussions remain fragmented and often focus on isolated dimensions of spirituality, morality, worship, or social behaviour. This study aims to develop a comprehensive understanding of how Islamic educational values collectively contribute to character formation. Employing a qualitative literature review approach, the study analysed classical Islamic scholarship, contemporary educational theories, and empirical studies published in national and international academic sources. Data were examined through thematic analysis and conceptual synthesis to identify recurring themes and patterns across the literature. The findings reveal three major dimensions underlying character formation in Islamic education: the spiritual-ethical foundation of character, the internalisation of values through worship and educational practices, and the manifestation of character through social responsibility. The analysis further demonstrates that tauhid, akhlaq, worship, and social responsibility function as interconnected and mutually reinforcing dimensions rather than separate educational components. Based on these findings, the study proposes an integrative conceptual framework that positions Islamic religious education as a holistic system of character formation. This framework contributes to the theoretical development of Islamic education and provides a foundation for future research, curriculum design, and character education policy in contemporary educational contexts